Eksplorasi Tumbuhan yang Berpotensi Sebagai Pestisida Nabati di Kawasan Savana dan Hutan Musim Taman Nasional Baluran - Lyra Nur Azizah; Yesi Noviliani; Fadiyah Nabilah; Syabrina Syahla Zulfaa Nazhifah; Chantika Putri Kusumawardani; Meiry Fadilah Noor; Evi Muliyah; Muhammad Ridwan (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Indonesia has a very high plant diversity, with potential for bio-pesticides among these plants. Baluran National Park is a location that potentially boasts a high level of plant diversity. This study explores the potential of plants as natural pesticides in the savanna Bekol and Musim forest of Baluran National Park. The research employed an exploratory descriptive method. The data collection was conducted through observation and documentation. A total of 54 species from 28 plant families were successfully identified. Twenty-three species from 13 families have the potential to be used as biopesticides. Fourteen species were found in the Bekol savanna, and 10 species were found in the Musim forest. Pesticide plants are most commonly found in the Fabaceae family. These plants contain various compounds that offer potential for controlling plant pests. Active compounds found in these plants, including alkaloids, flavonoids, and saponins, were highlighted as potential biopesticides. The research also emphasized the negative environmental impact of chemical pesticides and the potential of plant-based pesticides as an alternative. The findings offer valuable insights into the use of natural pesticides in modern agriculture.